2021
DOI: 10.1016/j.cmi.2021.02.008
|View full text |Cite
|
Sign up to set email alerts
|

Onset, duration and unresolved symptoms, including smell and taste changes, in mild COVID-19 infection: a cohort study in Israeli patients

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
72
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 81 publications
(87 citation statements)
references
References 28 publications
4
72
2
Order By: Relevance
“… 1 Nearly 15–20 per cent of the afflicted population have reported persistent olfactory dysfunction. 2 Yet, this is starkly different from the findings of a six-month psychophysical olfactory assessment study, in which 60 per cent of the cohort were found to have persistent olfactory dysfunction, whilst only 18 per cent of this group self-reported on altered smell. 3 Parallel to that, the prevalence of, as well as recovery from, olfactory dysfunction in Covid-19 patients may be underreported, as most study findings are based on self-reports.…”
Section: Introductioncontrasting
confidence: 66%
“… 1 Nearly 15–20 per cent of the afflicted population have reported persistent olfactory dysfunction. 2 Yet, this is starkly different from the findings of a six-month psychophysical olfactory assessment study, in which 60 per cent of the cohort were found to have persistent olfactory dysfunction, whilst only 18 per cent of this group self-reported on altered smell. 3 Parallel to that, the prevalence of, as well as recovery from, olfactory dysfunction in Covid-19 patients may be underreported, as most study findings are based on self-reports.…”
Section: Introductioncontrasting
confidence: 66%
“…[1][2][3][4][5] Estimates of symptom prevalence and persistence vary substantially, arguably due to heterogeneous study designs and syndrome definitions. [6][7][8][9] It has been suggested that Long COVID describes a group of disparate conditions, including post-viral syndromes, long-term tissue or organ damage and ongoing inflammation. 3,7,10,11 Occurrence of Long COVID appears to be associated with the severity of acute COVID-19 symptoms; for example, high prevalence of persistent symptoms has been reported among people hospitalised with COVID-19.…”
Section: Introductionmentioning
confidence: 99%
“…Most individuals (>75-80%) reporting taste and smell impairments due to COVID-19 tend to recover these senses within a few months, but smell impairment is still reported by 25-40% of patients after one or two months 5,14 at 6 months 15,16 . Given the common confusion between taste, smell and flavor, data on taste recovery are less clear, though suggested to recover somewhat faster than smell 16 .…”
mentioning
confidence: 99%
“…Most individuals (>75-80%) reporting taste and smell impairments due to COVID-19 tend to recover these senses within a few months, but smell impairment is still reported by 25-40% of patients after one or two months 5,14 at 6 months 15,16 . Given the common confusion between taste, smell and flavor, data on taste recovery are less clear, though suggested to recover somewhat faster than smell 16 . Separately, some individuals recover from acute smell loss, only to subsequently report other olfactory dysfunction, such as parosmia (smell distortions) and phantosmia (phantom smells or olfactory hallucinations) 17,18 .…”
mentioning
confidence: 99%